An intervention to improve sleep for people living with dementia: Reflections on the development and co-production of DREAMS:START (Dementia RElAted Manual for Sleep: STrAtegies for RelaTives). (November 2018) - Rapaport, Penny; Webster, Lucy; Horsley, Rossana; Kyle, Simon D; Kinnunen, Kirsi M; Hallam, Brendan; Pickett, James; Cooper, Claudia; Espie, Colin A; Livingston, Gill
Many people living with dementia experience sleep disturbances yet there are currently no known effective, safe and acceptable treatments. Working with those affected by dementia to co-produce interventions is increasingly promoted to ensure that approaches are fit for purpose and meet the specific needs of target groups. Our aim here is to outline and reflect upon the co-production of Dementia RElAted Manual for Sleep; STrAtegies for RelaTives (DREAMS:START), an intervention to improve sleep for people living with dementia. Our co-production team brought together experts in the development and testing of manualised interventions in dementia care and cognitive behavioural interventions for sleep disorders, with Alzheimer's Society research network volunteers (ASRNVs) whose lives had been affected by dementia. Here we present the process of intervention development. We worked with (ASRNVs) at each stage of the process bringing together 'experts by training' and 'experts by experience'. (ASRNVs)shared their experiences of sleep disturbances in dementia and how they had managed these difficulties, as well as suggestions for how to overcome barriers to putting the intervention into practice; making (DREAMS:START) more accessible and usable for those in need. In this paper we discuss both the benefits and challenges to this process and what we can learn for future work. Collaborating with 'experts by experience' caring for a relative with sleep difficulties helped us to develop a complex intervention in an accessible and engaging way which we have tested and found to be feasible and acceptable in a randomised controlled trial.